IMPACTS OF Xanthium strumarium L. INVASION ON VASCULAR PLANT DIVERSITY IN POTHWAR REGION (PAKISTAN) - Qureshi, H.; Anwar, T.; Arshad, M.; Osunkoya, O. O.; Adkins, S. W. (Annali di Botanica, 2019)
Studies on the impacts of alien plants help to understand extent of biological invasion. Multiple analyses of diversity parameters at different locations allow general explanations of impact on species diversity and richness in plant communities. The current study assessed impact of Xanthium strumarium invasion on native plant diversity in Pothwar region of Pakistan. The approach used for study was random samplings with two categorical factors: invaded and non-invaded plots under same habitat conditions. Differences in species frequency (N), species richness (R), evenness (Jꞌ), Shannon diversity index (Hꞌ) and Simpson index of dominance (λ) were compared between invaded and control plots by t-test series. Control plots harbored by average 1.3 more species/10m2. The control category was more diverse (Hꞌ=2.00) than invaded category (Hꞌ=1.82). Non-invaded plots showed a higher floristic richness than invaded ones. At multivariate scale, ordination (nMDS) and ANOSIM showed significant magnitude of differences between invaded and control plots. The decrease in diversity indices in invaded over control sites indicated that plant communities become less biodiverse due to Xanthium strumarium invasion. This makes X. strumarium a candidate of consideration for appropriate control measures.